2023
DOI: 10.1177/15330338221150318
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Receptor A2B Antagonist Inhibits the Metastasis of Gastric Cancer Cells and Enhances the Efficacy of Cisplatin

Abstract: Adenosine receptors play a key role in cancer progression. This study investigated the effect of the adenosine A2B receptor (ADORA2B) on epithelial–mesenchymal transition (EMT) markers and cell metastasis of gastric cancer (GC) cells. Public databases were used to investigate the specificity of ADORA2B expression in GC tissue. We used immunohistochemistry and immunofluorescence to detect ADORA2B expression in GC tissue, paracancerous tissue, and metastatic greater omental tissue. AGS and HGC-27 GC cells were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Similarly, genetic deletion of the Adora2b receptor in mouse and human triple-negative breast cancer cells reduces their metastatic capability in vivo (109), suggesting an important role for Adora2b in cancer metastasis. Recently, it was also shown that antagonizing Adora2b expression in gastric cancer cells increased the efficacy of cisplatin treatment (110). However, despite these promising results in melanoma, breast cancer, and gastric cancer cells, the specific role of Adora2b in metastatic development remains unknown.…”
Section: Adora2b Function In Metastasismentioning
confidence: 99%
“…Similarly, genetic deletion of the Adora2b receptor in mouse and human triple-negative breast cancer cells reduces their metastatic capability in vivo (109), suggesting an important role for Adora2b in cancer metastasis. Recently, it was also shown that antagonizing Adora2b expression in gastric cancer cells increased the efficacy of cisplatin treatment (110). However, despite these promising results in melanoma, breast cancer, and gastric cancer cells, the specific role of Adora2b in metastatic development remains unknown.…”
Section: Adora2b Function In Metastasismentioning
confidence: 99%